Perceived organizational support and gratitude towards employee organizational commitment - Repa, Meidiya Ende; Bashori, Khoiruddin; Sari, Erita Yuliasteti Diah (Empathy : Jurnal Fakultas Psikologi, 2024)
This study aims to examine the influence of perceived organizational support (POS) and gratitude on the organizational commitment of employees at RSUD dr M.Y. The sampling technique used was quota sampling, with 103 employees participating as subjects in the study. The instruments utilized included organizational commitment scale, perceived organizational support scale, and gratitude scale. Data analysis employed multiple linear regression. The results indicate a significant influence of both perceived organizational support and gratitude on organizational commitment at RSUD dr M.Y. Specifically, perceived organizational support does not significantly affect organizational commitment, whereas gratitude has a highly significant impact on organizational commitment. The conclusion drawn from this research is that higher levels of POS and gratitude jointly correspond to higher organizational commitment, and vice versa. However, independently, high or low levels of POS do not influence organizational commitment. Furthermore, higher levels of gratitude correlate with increased organizational commitment, while lower levels of gratitude correlate with decreased organizational commitment.